The concentration of heavy metals in the energy crops phytomass when grown in the conditions of Zhytomyr Polissia - Romanchuk, L.; Vyshnivskyi, P.; Mozharivska, I. (Agrobìologìâ, 2022)
The high level of anthropogenic pressure on agro-landscapes recently leads to an increased level of their contamination with heavy metals, which are among the most harmful chemical pollutants for the environment. Heavy metals are transmitted through trophic chains with a pronounced cumulative effect, in connection with which their toxicity can appear suddenly on individual links of trophic chains. The danger from heavy metals is determined by the fact that, unlike organic pollutants, they do not break down, but change from one form to another. Based on the results of the study, it was established that the accumulation of heavy metals by energy plants depended on the type of crop. Thus, it was proved that the concentration of heavy metals in energy crops plants when grown in the territory of radioactive contamination was within the limit of permissible concentrations. The lowest concentration of toxicants was noted when all energy crops were grown without fertilizers. The subject of the study was energy crops (Silhium perfoliatum L., Sorghum almum Parodi, Bunias orientalis L., Sida hermaphrodita Rusby, Miscanthus giganteus G.), heavy metals in plants, sod-podzolic sandy soil, mineral fertilizers. Therefore, the purpose of our research was to determine the phytomass of energy crops grown in areas contaminated with radionuclides as a result of the accident at the Chernobyl Nuclear Power Plant to determine the concentration of toxic substances. When performing the work, both general and special research methods were used: field – for conducting stationary and short-term field experiments, analytical – for determining the content of heavy metals in plants crops (Silhium perfoliatum L., Sorghum almum Parodi, Bunias orientalis L., Sida hermaphrodita Rusby, Miscanthus giganteus G.). The research was conducted during 2017−2020 on sod-podzolic soils in the territory of the village. Khrystynivka, Zhytomyr region, which belongs to the zone of unconditional (mandatory) resettlement (2nd zone of radioactive contamination). Prospects for further research will be aimed at establishing patterns of distribution of heavy metals in soil layers when growing energy crops. Key words: Silhium perfoliatum L., Sorghum almum Parodi, Bunias orientalis L., Sida hermaphrodita Rusby, Miscanthus giganteus G., lead, cadmium, copper, zinc.